Emerging Role of Sirtuin 2 in Parkinson’s Disease - Liu, Yumei; Zhang, Yingying; Zhu, Konghua; Chi, Song; Wang, Chong; Xie, Anmu (Frontiers in Aging Neuroscience, 2020)
Parkinson's disease (PD), the main risk factor of which is age, is one of the most common neurodegenerative diseases, thus presenting a substantial burden on the health of affected individuals as well as an economic burden. Sirtuin 2 (SIRT2), a subtype in the family of sirtuins, belongs to class III histone deacetylases (HDACs). It is known that SIRT2 levels increase with aging, and a growing body of evidence has been accumulating, showing that the activity of SIRT2 mediates various processes involved in PD pathogenesis, including aggregation of α-synuclein (α-syn), microtubule function, oxidative stress, inflammation and autophagy. There have been conflicting reports about the role of SIRT2 in PD, in that some studies indicate its potential to induce the death of dopaminergic neurons, and that inhibition of SIRT2 may therefore have protective effects in PD. Other studies suggest a protective role of SIRT2 in the context of neuronal damage. As current treatments for PD are directed at alleviating symptoms and are very limited, a comprehensive understanding of the enzymology of SIRT2 in PD may be essential for developing novel therapeutic agents for the treatment of this disease. This review will provide an update on our knowledge of the structure, distribution, and biological characteristics of SIRT2, and highlight its role in the pathogenesis of PD.